CONSTITUTIONAL DEMOCRACY AND ISLAM the legal status of muslims in italy. - Alicino, Francesco ([S.l.] : ROUTLEDGE, 2023)
This book outlines the legal status of Muslims in Italy. In particular, it highlights that, when it comes to Islam, the Italian legal system exacerbates the dilemma of contemporary constitutional democracies, increasingly caught between the principle of equality and the right to have rights, which implies the respect of diversity. It provides readers with a deep understanding of how domestic and external socio-political factors may muddle the interpretation of Italy's constitutional provisions, starting with those relating to state secularism and religious freedom. It is argued that today, as never before, these provisions are torn between the principle of equality and the right to be different. This situation has been exacerbated by incessant states of emergency, from immigration to religion-inspired terrorism, in light of which the presence of Islam in the peninsula has been highly politicized. Italy's experience on the legal status of Muslims provides an interesting case study and, as such, a valuable source of empirical information for a functioning and pluralistic constitutional democracy, especially when dealing with conditions of fear and insecurity. The book will be of interest to researchers, academics, and policy-makers working in the areas of law and religion, constitutional law, comparative law, and human rights.
Keywords: Muslims -- Legal status, laws, etc. -- Italy; LAW / Constitutional; RELIGION / Islam / Law